Proceedings of the 25th ACM International Conference on Multimedia 2017
DOI: 10.1145/3123266.3123331
|View full text |Cite
|
Sign up to set email alerts
|

What your Facebook Profile Picture Reveals about your Personality

Abstract: People spend considerable effort managing the impressions they give others. Social psychologists have shown that people manage these impressions differently depending upon their personality. Facebook and other social media provide a new forum for this fundamental process; hence, understanding people's behaviour on social media could provide interesting insights on their personality. In this paper we investigate automatic personality recognition from Facebook profile pictures. We analyze the effectiveness of fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 49 publications
2
40
0
12
Order By: Relevance
“…With regards to personality prediction, early efforts have shown that bag-of-visual-words and Facebook profile images could predict users' personality [68]. Various sets of features have been obtained from the images of 11,736 Facebook users were extracted to build a computational model which has more predictive power than human raters for predicting similar personality traits [69].…”
Section: Social Media and Image Analysismentioning
confidence: 99%
“…With regards to personality prediction, early efforts have shown that bag-of-visual-words and Facebook profile images could predict users' personality [68]. Various sets of features have been obtained from the images of 11,736 Facebook users were extracted to build a computational model which has more predictive power than human raters for predicting similar personality traits [69].…”
Section: Social Media and Image Analysismentioning
confidence: 99%
“…Work of Ferwerda, Schedl, and Tkalcic [11,13] on Instagram pictures, showed that the way filters are applied to create a certain distinctiveness can be used to predict personality traits of the poster. Others (e.g., [2,26]) have focused on the content of pictures. They showed that compositions of Facebook profile pictures consist of indicators of users' personality.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have discussed several major advantages of computers over humans in dealing with such classification problems. For example, segalin et al think that computers have the ability to store a large amount of information, which is difficult for humans to access [45]. Wei et al believe that computers can utilize a tremendous amount of information to optimize the judgmental accuracy, while humans may be affected by various biases sometimes [54].…”
Section: Learning Models and Performancementioning
confidence: 99%